LncRNA TUG1 alleviates cardiac hypertrophy by targeting miR‐34a/DKK1/Wnt‐β‐catenin signalling. Issue 6 (14th February 2020) - Fang, Qingxia; Liu, Ting; Yu, Chenhuan; Yang, Xiuli; Shao, Yanfei; Shi, Jiana; Ye, Xiaolan; Zheng, Xiaochun; Yan, Jieping; Xu, Danfeng; Zou, Xiaozhou
Abstract: The current study was designed to explore the role and underlying mechanism of lncRNA taurine up‐regulated gene 1 (TUG1) in cardiac hypertrophy. Mice were treated by transverse aortic constriction (TAC) surgery to induce cardiac hypertrophy, and cardiomyocytes were treated by phenylephrine (PE) to induce hypertrophic phenotype. Haematoxylin‐eosin (HE), wheat germ agglutinin (WGA) and immunofluorescence (IF) were used to examine morphological alterations. Real‐time PCR, Western blots and IF staining were used to detect the expression of RNAs and proteins. Luciferase assay and RNA pull‐down assay were used to verify the interaction. It is revealed that TUG1 was up‐regulated in the hearts of mice treated by TAC surgery and in PE‐induced cardiomyocytes. Functionally, overexpression of TUG1 alleviated cardiac hypertrophy both in vivo and in vitro. Mechanically, TUG1 sponged and sequestered miR‐34a to increase the Dickkopf 1 (DKK1) level, which eventually inhibited the activation of Wnt/β‐catenin signalling. In conclusion, the current study reported the protective role and regulatory mechanism of TUG1 in cardiac hypertrophy and suggested that TUG1 may serve as a novel molecular target for treating cardiac hypertrophy.